The histone deacetylase inhibitor PCI-24781 impairs calcium influx and inhibits proliferation and metastasis in breast cancer - Yang, Tianshu (Theranostics, 2021)
Histone deacetylases (HDACs) are involved in key cellular processes and have been implicated in cancer. As such, compounds that target HDACs or drugs that target epigenetic markers may be potential candidates for cancer therapy. This study was therefore aimed to identify a potential epidrug with low toxicity and high efficiency as anti-tumor agents. Methods: We first screened an epigenetic small molecule inhibitor library to screen for an epidrug for breast cancer. The candidate was identified as PCI-24781 and was characterized for half maximal inhibitory concentration (IC(50)), for specificity to breast cancer cells, and for effects on carcinogenesis and metastatic properties of breast cancer cell lines in vitro. A series of in silico and in vitro analyses were further performed of PCI-24781 to identify and understand its target. Results: Screening of an epigenetic inhibitor library in MDA-MB-231 cells, a malignant cancer cell line, showed that PCI-24781 is a potential anti-tumor drug specific to breast cancer. Ca(2+) related pathways were identified as a potential target of PCI-24781. Further analyses showed that PCI-24781 inhibited Gαq-PLCβ3-mediated calcium signaling by activating the expression of regulator of G-protein signaling 2 (RGS2) to reduce cell proliferation, metastasis, and differentiation, resulting in cell death in breast cancer. In addition, RGS2 depletion reversed anti-tumor effect and inhibition of calcium influx induced by PCI-24781 treatment in breast cancer cells. Conclusions: We have demonstrated that PCI-24781 is an effective anti-tumor therapeutic agent that targets calcium signaling by activating RGS2. This study also provides a novel perspective into the use of HDAC inhibitors for cancer therapy.